Application of western understanding of elementary space, principles of perspective to landscape painting in Malaysian visual arts / Ernesto Carlos Pujazon Patron - Pujazon Patron, Ernesto Carlos (2022)
The history of representing the landscape as a visual notion advocate that its origins may be traced back to the Renaissance period, when painters sought a visual portrayal of truth rather than being a vehicle for human subjectivity. In the history of European Renaissance, scholars trace this discovery to a Florentine architect and mason named Filippo Brunelleschi (1377-1446), who defined the technique of depicting objects from the picture plane in relation to the viewer's eyes. The approach used to portray this depiction has been the corn stone and the evolution of comprehending the physical visual space, the linear perspective, and other components of art. The research drive to develop a unique approach in identifying the application of elementary space, linear perspective principles within the Malaysian visual field of landscape painting. As an assumption in this process of examination and based on the lack of evidence in this particular field presented in the limitation of this study, this research is intended to contribute to the creation of a clear understanding by providing new insights into the present prevalent practices among Malaysian artists. The study is inspired by the need to create a distinct strategy to recognizing the application of elementary space and the rule of linear perspective within the Malaysian visual arts scene in the field of landscape painting. What compels Malaysian artists to apply Western studies of elementary space and linear perspective techniques in their landscape paintings. Based on the data and arguments offered, inferences would be reached. In this observational method, it is critical to take a step back and analyze the strategy chosen to reach concluding results. It is believed that the findings provide fresh information that may be used to advance other fields, future research such as digital landscape, color, and composition in paintings.